2019
DOI: 10.3389/fphar.2019.01449
|View full text |Cite
|
Sign up to set email alerts
|

Red Yeast Rice: A Systematic Review of the Traditional Uses, Chemistry, Pharmacology, and Quality Control of an Important Chinese Folk Medicine

Abstract: Red yeast rice (RYR), a Chinese traditional folk medicine produced by the fermentation of cooked rice kernels with a Monascaceae mold, Monascus purpureus, has long been used to treat blood circulation stasis, indigestion, diarrhea, and limb weakness in East Asian countries. This article provides a systematic review of the traditional uses, chemistry, biological activities, and toxicology of RYR to highlight its future prospects in the field of medicine. The literature reviewed for this article was obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 163 publications
(174 reference statements)
1
64
1
1
Order By: Relevance
“…In addition, diabetes is associated with several macro- and micro-vascular diseases. To increase blood circulation and prevent vascular complications, a blood regulation formula, including San-Qi, LipoCol Forte Capsules, Bu-Yang-Huan-Wu-Tang, or Dan-Shen, is commonly co-prescribed for patients with type 2 diabetes ( Figure 3 ) ( Ng, 2006 ; Jia et al, 2019 ; Zhao et al, 2019 ; Zhu et al, 2019 ). Because type 2 diabetes mellitus frequently co-exists with osteoarthritis ( Veronese et al, 2019 ), Gui-Lu-Er-Xian-Jiao is often given to support the kidney yin and yang for patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diabetes is associated with several macro- and micro-vascular diseases. To increase blood circulation and prevent vascular complications, a blood regulation formula, including San-Qi, LipoCol Forte Capsules, Bu-Yang-Huan-Wu-Tang, or Dan-Shen, is commonly co-prescribed for patients with type 2 diabetes ( Figure 3 ) ( Ng, 2006 ; Jia et al, 2019 ; Zhao et al, 2019 ; Zhu et al, 2019 ). Because type 2 diabetes mellitus frequently co-exists with osteoarthritis ( Veronese et al, 2019 ), Gui-Lu-Er-Xian-Jiao is often given to support the kidney yin and yang for patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to this mechanism of action, it is called “natural statin”. Red yeast rice is also rich in pigments, organic acids, flavonoids, and natural phytosterols that contribute to the lipid-lowering action [ 251 , 252 ], namely reducing total cholesterol, LDL-C and TG. These results suggest that red yeast rice is an excellent oral food supplement without side effects, useful for the treatment of dyslipidemia, in particular in subjects intolerant to statins [ 253 ].…”
Section: Possible Effects Of Natural Bioactive Compounds In Metabomentioning
confidence: 99%
“…Pharmacokinetic studies propose that red yeast rice monacolin K exhibits poor bioavailability after oral administration, less than 5%. This is mainly due to an important intestinal and hepatic metabolism [ 251 ]. However, the monacolin K bioavailability would appear to be higher if assumed through the food matrix than as oral food supplement.…”
Section: Possible Effects Of Natural Bioactive Compounds In Metabomentioning
confidence: 99%
“…It has also been reported that fermented rice bran with Monascus increases phenolic acid and enhances antioxidant activity [ 21 , 22 ]. In addition, organic acids, amino acids, sterols, decalin compound derivatives, flavonoids, lignans, coumarins, terpenoids, and polysaccharides are reported as components contained in red yeast rice [ 23 ].…”
Section: Polyketides and Other Metabolites Produced In Monascus Fumentioning
confidence: 99%